Analisa Perancangan Sistem Aplikasi Kontrol Imunisasi Balita Berbasis Android Dengan Menggunakan Unified Language Modelling (UML) - Bermiko Kasah Padang; M.Alif Fahrezy; Abdul Halim Hasugian (JURNAL ILMIAH NUSANTARA, 2024)
Immunization is a process of strengthening the immune system by administering a vaccine, which is a virus or bacteria that has been weakened, killed or modified. Vaccination can be done by injection or orally. After the vaccine is inserted into the body, the body's defense system responds by producing antibodies, forming an immune system against certain types of viruses and bacteria. The purpose of creating this application is to build an android-based application to control the immunization of toddler growth and development. The research method section consists of data collection methods and system development methods. Observation, literature study and system design. This research produces an immunization data monitoring application intended for parents and Integrated Service Post officers at the Health Center